2015
DOI: 10.4067/s0718-58392015000500014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of straw mulching on maize photosynthetic characteristics and rhizosphere soil micro-ecological environment

Abstract: Straw mulching is an effective measure to improve soil properties, crop growth, and yield. To further understand the advantage mechanisms of straw mulching, a field experiment with seven straw mulching levels (0 to 18 000 kg ha -1 ) was conducted to study the effects of straw mulching on maize (Zea mays L.) photosynthesis and rhizosphere soil microecological environment. Results showed that maize chlorophyll content was evidently affected by straw mulching, and the highest chlorophyll content was at 12 000 kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 29 publications
6
10
0
Order By: Relevance
“…The plots with addition of straw had higher values of enzymatic activity, microbial biomass and respiration, reaching similar values to soil under native vegetation (García-Orenes et al 2010). However, straw mulch effect on enzymes activities was strongly dependent on mulching levels and some adverse effects at straw mulching higher than 15,000 kg ha -1 were observed (Zhang et al 2015). Straw mulch effect on soil enzymatic activity was also dependent on soil compaction level (Siczek and Frąc 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The plots with addition of straw had higher values of enzymatic activity, microbial biomass and respiration, reaching similar values to soil under native vegetation (García-Orenes et al 2010). However, straw mulch effect on enzymes activities was strongly dependent on mulching levels and some adverse effects at straw mulching higher than 15,000 kg ha -1 were observed (Zhang et al 2015). Straw mulch effect on soil enzymatic activity was also dependent on soil compaction level (Siczek and Frąc 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It can also reduce rice effective panicles per unit area, while number of spikelets per panicle, ripening rate, and rice yield can increase (Xu et al, 2015). The appropriate amount and burial depth of SR to increase rice yield have been at approximately 9 t ha -1 and 5-8 cm, respectively (Curtin and Fraser, 2003;Zhang et al, 2015). Although there is adequate information about the effects of SR on rice growth and yield, most studies have researched its impact under flooding irrigation (FI).…”
Section: Introductionmentioning
confidence: 99%
“…For the chlorophyll content, several studies have reported that black plastic mulching results in a greater value of chlorophyll content than control treatment [39][40][41]. Marichamy et al [42] and Yang et al [43] reported that black plastic mulching had the highest value of chlorophyll than organic mulches and found the lowest value of the control treatment. Zhang et al [44] also reported that straw mulching significantly increased the chlorophyll content compared to no mulching.…”
Section: Tree Growthmentioning
confidence: 99%